THE EFFECT OF APPLYING MEDIA ON THE STUDENTS ABILITY IN WRITING DESCRIPTIVE TEXT AT SMP NEGERI 1 TANAH JAWA - Partohap S. R Sihombing (Jurnal Dinamika Pendidikan, 2016)
In teaching English at school, the teacher must be able to find the best way in teaching the language skills especially Writing, so that the material given can be received well. This research used the quantitative analysis to find the effect of using pictures on student’s writing descriptive paragraph. In this thesis, the writer took 60 students as a sample of data. The populations were the second year of SMP Negeri 1 Tanah Jawa where the X-1 as the experimental group and X-2 as the control group. To collect the data, the writer applied writing test. It is an objective test. The validity of the instrument is found out by using the Coefficient ProductMoment Formula and the Formula of Spearman Brown to find out the reliability. The data were analyzed by using the t-Test. The finding indicates that pictures give an effect on student’s writing descriptive text. The research of the t-Test is 10,9. It means that the test is higher than the table (10,9>0,01). It can be said that there is an effect of pictureson student’s writing descriptive text. From the result of analysis, the writer concludes that : (1) The use of pictures give a positive effect in writing descriptive text, (2) The score of experimental group is higher than the score of control group, (3) The score of the t-observe calculation is higherthan t-table. So, the effect of using pictures on student’s writing descriptive text is accepted.Keywords : descriptive paragraph, standardized test, descriptive text